(untitled) (Clinics, 2008)
INTRODUCTION: Gynoid lipodystrophy (cellulite) has been cited as a common dermatological alteration. It occurs mainly in adult women and tends to gather around the thighs and buttocks. Its presence and severity have been related to many factors, including biotype, age, sex, circulatory changes, and, as some authors have suggested, mechanical alterations such as lumbar hyperlordosis. OBJECTIVE: To correlate the degree of cellulite with the angle of lumbar lordosis in asymptomatic women. METHODS: Fifty volunteers were evaluated by digital photos, palpation, and thermograph. The degree of cellulite was classified on a scale of 1-4. Analyses were performed on the superior, inferior, right and left buttocks (SRB, IRB, SLB, ILB), and the superior right and left thighs (SRT, SLT). The volunteers underwent a lateral-view X-ray, and the angle of lumbar lordosis was measured using Cobb's method (inferior endplate of T12 and the superior endplate of S). The data were statistically analyzed using ANOVA and Spearman's correlation. A significance level of 5% was adopted. RESULTS: Volunteers had a mean age of 26.1 ± 4.4 years and a mean body mass index of 20.7 ± 1.9 kg/m². There was no significant difference in lumbar lordosis angle between those with cellulite classes 2 and 3 (p >; 0.297). There was also no correlation between lumbar lordosis angle and the degree of cellulite (p >; 0.085 and r >; 0.246). CONCLUSIONS: The analysis suggests that there is no correlation between the degree of cellulite and the angle of lumbar lordosis as measured using Cobb's method.